Inotropes Score (IS) And Vasoactive Inotropes Score (VIS) After Congenital Heart Disease Surgery: Association and Outcome at PCICU of A Tertiary Cardiac Hospital - A, Talha; S, Kabir; T, Afrin; N, Tabassum; NA, Hasan (Bangladesh Journal of Medical Science, 2025)
Background and objectives Children with congenital heart diseases (CHD) undergoing surgical correction are at high risk for serious post‑operative morbidity and mortality. This study was conducted to figure out the association of inotropes score (IS) and vasoactive inotropes score (VIS) with clinical outcomes after congenital heart surgery. Materials and methods This is a retrospective observational study (total study population 477, April- December 2017) were done in a pediatric cardiac ICU (PCICU) of a tertiary cardiac hospital. Along with several demographic, operative and post‑operative variables, doses of inotropic and vasoactive medications were documented for the first 48hrs after PCICU admission. Maximum IS and VIS level in the first 48hrs was also recorded. Linear and multivariant regression analyses were done to find the association of IS / VIS with pre‑operative, intra‑operative and post‑operative variables in order to determine the association between IS / VIS and clinical outcome after pediatric cardiac surgery. Results A total 477 patients underwent cardiac surgery for CHD during the study period and among them 5.4% (3) neonate, 14.67% (70) infant and 80.08% (382) were children. Optimum cut-off value of high IS and VIS was detected by ROC curve, 7.2 (sensitivity 58%, specificity 94%) and 17.5 (sensitivity 86%, specificity 92%) respectively. Study population with early age, high level of cardiac complexity, high CPB time, high cross clamp time, kept open sternum in post-operative period were strongly associated with high VIS (≥17.5) level and statistically significant (p value <0.001). On linear regression analysis patient with high VIS level had more incidence of re-intubation, prolong period ventilation, prolong ICU stay, higher incidence AKI and high mortality and all were found statistically significant (p-value <0.05).Low body weight at the time of surgery, higher cardiac complexity, high CPB and cross clamp time, open sternum in post-operative period were strongly associated high IS (p value <0.05). Similarly, needed re-open after surgery, higher re-intubation, prolong ventilation, prolong ICU stay and high mortality were statistically significant with high IS level (p-<0.05). On multiple regression analysis revealed longer CPB time, needed kept open sternum after surgery, longer cross cIamp time was a self-dependent risk factor for high level of IS and VIS respectively. Both high level of IS and VIS is an important predictor for re-intubation after extubation whether VIS was an independent predictor of prolong duration of mechanical ventilation and mortality, was found to be statistical significant (p-value <0.05). Conclusions: Patients with high IS and VIS was strongly associated with early age of surgery, high cardiac complexity, increasing CPB and cross clamp time; and required prolong mechanical ventilator support, prolong ICU stay, suffered from increased morbidity and mortality. BJMS, Vol. 24 No. 03 July’25 Page : 923-930